Let [tex]P(n)[/tex] be the statement that
[tex]1\cdot1!+2\cdot2!+\cdots+n\cdot n!=(n+1)!-1[/tex]
For [tex]n=1[/tex], we have [tex]P(1)[/tex] true, since
[tex]1\cdot1!=1[/tex]
and
[tex](1+1)!-1=2!-1=2-1=1[/tex]
Assume [tex]P(k)[/tex] is true. Then
[tex]1\cdot1!+2\cdot2!+\cdots+k\cdot k!=(k+1)!-1[/tex]
Then for [tex]n=k+1[/tex] we have
[tex]1\cdot1!+2\cdot2!+\cdots+k\cdot k!+(k+1)\cdot(k+1)!=(k+1)!-1+(k+1)\cdot(k+1)![/tex]
because [tex]P(k)[/tex] is assumed to be true, then
[tex](k+1)!-1+(k+1)(k+1)!=(k+1)!(1+(k+1))-1=(k+2)\cdot(k+1)!-1=(k+2)!-1[/tex]
and so [tex]P(n)[/tex] is true for all [tex]n[/tex]. QED
Alternatively, no induction is needed, since
[tex](n+1)!=(n+1)\cdot n!=n\cdot n!+n![/tex]
so
[tex]1\cdot1!+2\cdot2!+\cdots+n\cdot n!=(2!-1!)+(3!-2!)+\cdots+((n+1)!-n!)=(n+1)!-1![/tex]
[tex]\implies1\cdot1!+2\cdot2!+\cdots+n\cdot n!=(n+1)!-1[/tex]